A Microfluidic Platform to Study Astrocyte Adhesion on Nanoporous Gold Thin Films - Alexander E. Hampe; Zidong Li; Sunjay Sethi; Pamela J. Lein; Erkin Seker (Nanomaterials, 2018)
Nanoporous gold (np-Au) electrode coatings have shown improved neural electrophysiological recording fidelity in vitro, in part due to reduced surface coverage by astrocytes. This reduction in astrocytic spreading has been attributed to the influence of electrode nanostructure on focal adhesion (FA) formation. This study describes the development and use of a microfluidic flow cell for imposing controllable hydrodynamic shear on astrocytes cultured on gold surfaces of different morphologies, in order to study the influence of nanostructure on astrocyte adhesion strength as a function of np-Au electrode morphology. Astrocyte detachment (a surrogate for adhesion strength) monotonically increased as feature size was reduced from planar surfaces to np-Au, demonstrating that adhesion strength is dependent on nanostructure. Putative mechanisms responsible for this nanostructure-driven detachment phenomenon are also discussed.